THE INFLUENCE OF SOCIAL MEDIA ON ADOLESCENTS' IDENTITY CONSTRUCTION A CRITICAL ANALYSIS - Muhtar; Sandra I. Telussa (Adisam Publisher, 2026)
This research aims to critically analyze the influence of social media on the identity construction process of teenagers in the digital era. Through a comprehensive literature review, this study explores the complexities and nuances of the interactions between social media use and adolescent identity development. The research methodology involves a systematic search and in-depth analysis of a variety of academic sources, including scientific journals, books and relevant research reports. These sources are selected based on their relevance, credibility, and novelty to provide a broad understanding of the topic. The research results reveal that social media plays a significant role in adolescent identity formation, offering a platform for self-exploration, expression, and social connection. However, this research also highlights the potential negative consequences of excessive engagement in social media, such as pressure to conform, social anxiety, and the formation of a fragmented identity. Further critical analysis explores the long-term implications of teens' digital footprints on social media, as well as the critical role of digital literacy and online reputation management in navigating this complex landscape. This study emphasizes the need for a collaborative approach involving youth, parents, educators, and society to support healthy identity development in the digital era. This research provides valuable insight into the influence of social media on adolescents' identity construction and highlights the need for comprehensive strategies to empower adolescents to harness the positive potential of social media while addressing its risks. The findings from this literature study provide a strong foundation for further research and the development of effective interventions to support healthy adolescent identity development in the digital era.